Prognostic Significance of HbA 1c Level in Asian Patients with Prediabetes and Coronary Artery Disease - Yang Liu; Xunxun Feng; Jiaqi Yang; Tienan Sun; Guangyao Zhai; Qianyun Guo; Yujie Zhou (Cardiovascular Innovations and Applications, 2022)
Background: Measuring glycosylated hemoglobin (HbA 1c ) is a simple way to assess patients with prediabetes or diabetes mellitus. It has been shown that HbA 1c level predicts prognosis in patients with coronary artery disease (CAD) and the incidence of diabetes mellitus. However, the prognostic significance of HbA 1c level in Asian patients with prediabetes and CAD is not yet clear. Our study aimed to determine the relationship between HbA 1c level and major adverse cardiovascular events (MACE) in patients with prediabetes and CAD. Methods: We enrolled 1367 patients with prediabetes and CAD in the final analysis, and grouped them according to the HbA 1c level. Primary end points included nonfatal myocardial infarction, hospitalization for unstable angina, and ischemia-driven revascularization. Cox proportional-hazards regression analysis was used to determine the relationship between HbA 1c level and MACE after our accounting for confounding factors. Results: A total of 1367 patients (age 58.8 ± 10.3 years; 71.6% men) were included. During 43 months of follow-up, 197 patients experienced at least one primary end point event. Multivariate Cox proportional-hazards regression analysis showed in comparison of HbA 1c levels that the hazard ratio for primary end points was 4.110, with a 95% confidence interval of 2.097–6.011 (P<0.001). Conclusions: HbA1c level positively correlated with MACE, demonstrating it is a valuable indicator for independently predicting MACE in Asian patients with prediabetes and CAD.